Drought tolerance monitoring of apple rootstock M.9-T337 based on infrared and fluorescence imaging - D.T. GAO; C.Y. SHI; Q.L. LI; Z.F. WEI; L. LIU; J.R. FENG (Photosynthetica, 2021)
Apple rootstock seedling M.9-T337 was selected to explore the effect of drought stress. The findings indicated that the relative water content of both the leaf and soil gradually decreased with an increase in drought stress. The water-use efficiency of the leaves increased gradually but decreased sharply after 20 d of drought. Changes in the gas-exchange parameters and chlorophyll fluorescence parameters reflected the gradual decrease in the photosynthetic capacity of the plants with drought stress duration. Infrared thermal imaging showed significant temperature differences between the drought-stressed and control plants after 15 d of drought treatment. When irreversible damage occurred under drought stress, the crop water-stress index and relative water content of the leaf and soil were 0.7, 60.5, and 17.8%, respectively. Based on the results, we formulated a drought stress-grade standard. Further, we established that the best time for irrigation is when drought stress reaches grade 3.